Visualization of Defects on a Cultured Cell Layer by Utilizing Chemical Imaging Sensor - Miyamoto, Ko-ichiro; Bing, Yu; Wagner, Torsten; Yoshinobu, Tatsuo; Schöning, Michael J. (Procedia engineering, 2015)
The chemical imaging sensor is a field-effect sensor which is able to visualize both the distribution of ions (in LAPS mode) and the distribution of impedance (in SPIM mode) inthe sample. In this study, a novel wound-healing assay is proposed, in which the chemical imaging sensor operated in SPIM mode is applied to monitor the defect of a cell layer brought into proximity of the sensing surface.A reduced impedance inside the defect, which was artificially formed ina cell layer, was successfully visualized in a photocurrent image.